Persepsi Siswa MP Kelas X Mengenai penggunaan Media Sosial Instagram dalam Meningkatkan Citra SMK Sandikta - Ayu Wulandari; Murtiadi Murtiadi; Roynaldi Arista (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to explore the positive perceptions of Office Management grade X students regarding the use of the Instagram account @osissmksandikta in efforts to enhance the image of SMK Sandikta. The background of this research is based on the importance of social media as a means of public communication in the digital era, particularly in building the reputation of educational institutions among the younger generation. The OSIS Instagram account is viewed as the school’s representation in delivering information, promoting activities, and creating emotional engagement between the student organization and both internal and external audiences. The research employed a qualitative descriptive approach. Data collection techniques included in-depth interviews, participatory observation, and documentation to obtain comprehensive findings. The informants consisted of one key informant, namely the OSIS advisor, and three main informants who were Office Management grade X students. Informants were selected purposively, considering their direct involvement with the OSIS Instagram account. The findings reveal that the @osissmksandikta Instagram account is perceived as effective in building a positive school image through the presentation of engaging visual content, a communication style suited to student characteristics, and the provision of relevant, easily accessible information. The account also fosters a sense of involvement and pride since its management is carried out alternately by OSIS members, thereby strengthening collective ownership. Furthermore, active student participation in responding to content reinforces the relationship between the school and its students. The study concludes that the use of Instagram can serve as an effective medium for enhancing a school’s positive image if managed consistently, interactively, and in alignment with the needs and preferences of the target audience. This finding is expected to contribute to the development of school communication strategies through social media.